1980
DOI: 10.1016/0022-4804(80)90074-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of portacaval shunt upon hepatic cholesterol synthesis and cyclic AMP in dogs and baboons

Abstract: Hepatic cholesterol synthesis, hepatic cyclic AMP, and portal and peripheral insulin and glucagon levels were investigated in nine dogs and three baboons after complete portacaval shunt. Cholesterol synthesis as measured with acetate incorporation was reduced in both species. Hepatic cyclic AMP increased in dogs. Changes in portal and systemic insulin were inconsistent, but hyper-glucagonemia occurred regularly. Diminished hepatic cholesterol synthesis is apparently one factor, although probably not the only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…pes causes a reduction in cholesterol synthesis (6,13,(23)(24)(25)(26)(27)(28)(29)(30) and bile acid synthesis (13,24,30,31). Interruption of the venous enterohepatic circulation has been one presumed cause of the elevation in postprandial serum bile acids caused by pes (12,13).…”
Section: Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…pes causes a reduction in cholesterol synthesis (6,13,(23)(24)(25)(26)(27)(28)(29)(30) and bile acid synthesis (13,24,30,31). Interruption of the venous enterohepatic circulation has been one presumed cause of the elevation in postprandial serum bile acids caused by pes (12,13).…”
Section: Nsmentioning
confidence: 99%
“…\ 4 7) have seen similar cumulative effects in dogs after portal diversion (by means of portacaval transposition) plus ileal resection. However, it is theoretically possible that procedures such as IB, BF, and ileal resection, which increase the enteric losses as well as the hepatic synthesis of cholesterol and bile acids, could subvert the antilipidemic mechanisms of pes which are thought to derive mainly from depressed hepatic cholesterol synthesis (3,6,13,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Nsmentioning
confidence: 99%
“…In our initial investigations of this possibility, we demonstrated reductions of more than 80% in canine hepatic cholesterol and triglyceride synthesis. 17 Although a similar diminution in cholesterol and/or lipoprotein synthesis was confirmed in rats, [67][68][69] dogs, 70 swine, [71][72][73] and baboons, 70 not all workers could verify these findings. The rigorously controlled studies in rats by Proia et al, 68 which are the only reported animal experiments concerning Eck's fistula and lipid synthesis in which body weights were maintained or increased postoperatively, have done much to explain the discordant reports.…”
Section: Biochemical Parametersmentioning
confidence: 96%
“…Note that all 36 values are below the consensus TC of 100 pM for activating AC (see Figure 4). The 36 sources were: Kraft et al (2017), Lewis et al (1997), Saccà et al, (1979) and Vaitkus et al, (1984), (10–19); Berger et al (1994), Blommaart et al (1995), Curnow et al (1976), Fries et al (1982), Hickman et al (1992), Imai et al (2003) and Wasserman et al (1993) (20–29); Androgué et al (1985), Baumann et al (1981), Cersosimo et al (1989), Rao (1995) and Sherwin et al (1977) (30–39); Francavilla et al (1980), Holst et al (1980), Langhans et al (1984) and Müller et al (1984) (40–49); Demigné et al (1985), Goldstein and Curnow (1978), Horikawa et al (1998), Jaspan et al (1984), Silva et al (1990) and Wolf and Eisenstein (1981), (50–59); Balks and Jungermann (1984), Gannon and Nuttall (1993), Ishida et al (1981), Kinoshita et al (1985), McLeod et al (1983), Rabouti et al (1989) and Silva et al (1990) (60–69); Hussein et al (1986), Latour et al (1999) and Okuda et al (1994) (70–79)…”
Section: Plasma Glucagon Concentrationsmentioning
confidence: 99%